2022
DOI: 10.52184/msrmr.v12i01.101
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Organizational Justice and Organizational Citizenship Behaviour: A Case Study of Wipro

Abstract: Every organization’s existence is aimed at designing their operations in the pursuit of making monetary benefits through vision and mission. Letting employees understand the vision and goal of the organization helps the employee to understand the ideas and milestones of the organizations. Work from home scenario across industries has brought in a new challenge to communication connectivity with the workforce. Organizations have to communicate not only their goals to the employees but also should gain the trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…Patients included in the study were periodontally healthy and there was no statistical difference in periodontal status between groups. This is an expected outcome for patients with cooperation and good oral hygiene and is consistent with the results of other studies Charavet et al 14 .…”
Section: Harold Frostsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients included in the study were periodontally healthy and there was no statistical difference in periodontal status between groups. This is an expected outcome for patients with cooperation and good oral hygiene and is consistent with the results of other studies Charavet et al 14 .…”
Section: Harold Frostsupporting
confidence: 93%
“…It is not known whether rapid tooth movement increases gingival recession. Charavet et al 14 . reported that overall recession scores did not increase after treatment in both accelerated group and control group…”
Section: Harold Frostmentioning
confidence: 99%